Practicing Care-Centered Leadership in a Pandemic: Narratives and Notes on Care Ethics Experiences and Practices in Extraordinary Times - Schultz, Christie (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2022)
This case explores experiences of practicing care-centered leadership during the COVID-19 pandemic. The case narrative is the author’s anonymized account of responding with care ethics to specific challenges encountered during the pandemic and the complexities of transitioning into a new leadership role in 2020. The teaching notes and activities invite readers to consider the ways in which care-centered leadership practices might continue beyond pandemic times by asking: In what ways might pandemic-enabled compassion for students be sustained post-pandemic; in what ways might flexibility for teaching and learning modalities persist; and how has this crisis offered an opportunity to critically examine the ways in which we lead in educational settings?